Muslim academicians' attitudes toward offensive television advertisements on health and beauty products / Maisarah Ishak …[et al.] - Ishak, Maisarah; Ahmad Zaini, Azniza; Mustapha, Musramaini; Hussin, Adibah; Tajuddin, Norulhuda (2012)
The awareness of offensive television advertisements among Muslim consumers especially in Malaysia is still uncommon. Thus, this paper aims to identify the Muslim academicians' attitudes towards offensive television advertisements on health and beauty products based on marital status. Furthermore, the researchers would like to investigate the difference of perception towards television advertisement on health and beauty products based on five (5) different television advertisements in Malaysia. Self-administered questionnaires were distributed to academic staff from various faculties in UiTM Pahang using convenience sampling technique. Six (6) reasons selected for offensive including; concern for children, health and safety issues, language, sexist images, stereotyping of people and subject too personal were used to indicate each of the advertisements. The findings show Muslim academicians from different marital status feel offended on different reasons and gave their own positive and negative perception toward the selected television advertisements.